Capacidade institucional para integração das políticas urbanas de regularização fundiária, prevenção de conflitos e melhorias habitacionais e sanitárias na Amazônia Legal - BARROS, Vanessa Cunha (2022)
From the Federal Constitution of 1988 onwards, municipalities assumed a leading role in the development and implementation of public policies, however this role has been facing difficulties in putting into practice their new competences, since most Brazilian municipalities do not have institutional capacity. to execute its urban public policies in an integrated way. This work aims to analyze the municipal institutional capacity to promote actions to guarantee the right to the city in an integrated way in the municipalities that received areas of the Terra Legal Program and are part of the Amazon Network Program. For the analysis, the matrix of urban nonconformities of Santos (2018) was used and it was proved that Brazilian municipalities, especially those located in the Legal Amazon, have a low institutional capacity to implement integrated urban public policies, a since most do not have administrative, technical and instrumental resources.